Treatment of Chronic Traumatic Diaphragmatic Hernia Based on Laparoscopic Repair: Experiences From 23 Cases - Liu, Qiaonan; Luan, Li; Zhang, Guangyong; Li, Bo (Frontiers in Surgery, 2021)
Background: We aimed to investigate the safety and effectiveness of laparoscopic repair for treating chronic traumatic diaphragmatic hernia (CTDH). Methods: In this retrospective analysis, we included 23 cases with CTDH underwent laparoscopy in our hospital between June 2015 and October 2019 was performed. The patient characteristics were recorded. We compared the diameter of hernia ring, surgery duration, intraoperative bleeding volume, means of repairing, as well as the follow-up data. Results: All the patients underwent laparoscopic diaphragmatic hernia repair, without conversion to laparotomy or thoracotomy. The operation time ranged from 60 min to 200 min (mean, 108.04±42.93 min). The blood loss volume ranged from 10 ml to 300 ml (mean volume, 63.48±71.69 ml). The postoperative hospital stayed ranged from 5 days to 15 days (mean, 6.22±2.11 days). The patients were followed up for 1-50 months (mean, 17.5 ±10.90 months). No recurrence of diaphragmatic hernia was found. Conclusions: Laparoscopic repair of CTDH is featured by fast recovery, high security and effectiveness. Reducing the hernia contents and close of the hernia ring are crucial for the surgery that is performed based on the size and location of the diaphragmatic hernia.